1967
DOI: 10.1111/j.1471-4159.1967.tb09512.x
|View full text |Cite
|
Sign up to set email alerts
|

Triphosphoinositide Phosphomonoesterase Activity in Nerve Cell Bodies, Neuroglia and Subcellular Fractions From Whole Rat Brain

Abstract: SLOANE -STANLEY (1953) first showed that brain homogenates hydrolysed inositol lipids. The further study of RODNIGHT (1956) suggested that two enzymes, a phosphomonesterase and a phosphodiesterase were present. Extracts of ox brain have yielded purified enzymes of both the monoesterase and diesterase type which attack triphosphoinositide (TPI) (DAWSON and THOMPSON, 1964; THOMPSON and DAWSON, 1964a, b).A method has now been developed (HENDRICKSON and BALLOU, 1964) for the preparation of a purer triphosphoinosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
3

Year Published

1968
1968
1976
1976

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 3 publications
3
16
3
Order By: Relevance
“…Alkaline and acid phosphatase assays are described in the text. most of the activity in the supernatant fraction, which would tend to confirm the results found for brain (Salway et al, 1967;Harwood & Hawthorne, 1969), but contradict those of Lee & Huggins (1968a,b) who claimed the kidney enzyme to be microsomal. The recovery of the enzyme was high, suggesting latency, but freezing and thawing did not increase activity.…”
Section: Methodscontrasting
confidence: 52%
See 1 more Smart Citation
“…Alkaline and acid phosphatase assays are described in the text. most of the activity in the supernatant fraction, which would tend to confirm the results found for brain (Salway et al, 1967;Harwood & Hawthorne, 1969), but contradict those of Lee & Huggins (1968a,b) who claimed the kidney enzyme to be microsomal. The recovery of the enzyme was high, suggesting latency, but freezing and thawing did not increase activity.…”
Section: Methodscontrasting
confidence: 52%
“…Similarly, Santiago-Calvo et al (1964) found a high turnover of the phosphoinositides in various tissues. Phosphatidylinositol bisphosphate phosphatase (EC 3.1.3.36) has been investigated in brain (Dawson & Salway et al, 1967;Sheltawy et al, 1972) and kidney (Lee & Huggins, 1968a,b), but work on the subcellular distribution of this enzyme has led to conflicting observations. Salway et al (1967) and Harwood & Hawthorne (1969) studying brain found that triphosphoinositide phosphatase was localized in the particle-free cytoplasmic fraction.…”
mentioning
confidence: 99%
“…The subcellular distribution of triphosphoinositide phosphomonoesterase is very similar to that of the kinase (Salway et al 1967b). …”
Section: Methodsmentioning
confidence: 56%
“…The kinase activity would appear less if triphosphoinositide phosphomonoesterase was activated by the univalent ions. Activation is possible under certain conditions (Dawson & Thompson, 1964), but the supernatant phosphomonoesterase can be inhibited by Na+ ions under other conditions (Salway et al 1967b). Hayashi, Yagihara, Nakamura & Yamazoe (1966) showed that the incorporation of [32P]P5 into the lipids of guinea-pig brain slices increased when the slices, which had been incubated in Na+-free choline-Ringer solution, were transferred to normal Ringer solution for a further incubation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation